INTEGRATION MODEL OF CONSERVATION AREA EFFECTIVENESS AND FISHERIES MANAGEMENT STATUS: CASE OF SMALL ISLAND PARKS KEI KECIL - James Abrahamsz; Tofik Alansar; Taufik Abdillah; Marvin M. Makailipessy; Imanuel M. Thenu (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The need of Small Island Park (SIP) management at Kei Kecil Islands and improvement of fisheries management, stems from the question of whether conservation can improve fisheries management. Doubts of the benefits of conservation areas in addressing fisheries management issues, as well as poor planning, monitoring and evaluation, have the potential to create disincentives and low expectations of management. This study aims are to assess the effectiveness of SIP management, fisheries management status, and formulate an integrated model of improved management of conservation areas and fisheries. The effectiveness of conservation area management was in the red rank. For two years, these developments were relatively slow. The status of fisheries management in the medium category. The Kobe Plot analysis recommended to management by maintaining the existing strategy. Scenario to improve management through the determination of 80% of indicators are in good condition, the opportunity to achieve well management within 3 - 4 years. Based on integration model, multi-level assessment of effectiveness had a weakness in answering its relationship with fisheries management. The strength of the integration model in the grouping of management objectives according to sustainable management system, including: ecological protection, social strengthening and dynamic and accommodative governance system. Keywords ecological, social, governance, model